Peningkatan Kemandirian Lansia Melalui Okupasi Terapi dan Group Psychotheraphy di PSTW Sabai Nan Aluih Sicincin Padang Pariaman - Sunardi Sunardi; Renidayati Renidayati (Poltekkes Kemenkes Padang, 2020)
The increasing number of the elderly causes complex problems for the elderly, families and communities. Physiological and psychological changes make the elderly feel useless, experience decreased motivation and independence. One of the efforts to increase the independence of the elderly in order to remain qualified is the application of therapeutic modalities in the form of occupational therapy and group psychotherapy. This study aims to determine the changes in the independence of the elderly before and after Ocupasi therapy and Group Psychotherapy at PSTW Sabai Nan Aluih Sic Cincin, Padang Pariaman Regency. The study used a quantitative approach with